METHODOLOGICAL ASPECTS OF TEACHING NATURAL SCIENCES IN DISTANCE EDUCATION (Ecological Bulletin of Kryvyi Rih District, 2024)
Distance education is becoming increasingly important in the lives of students, which affects the change of methods, means and approaches to learning. Online education has been actively developing for quite a long time. In general education institutions, this is a new form of knowledge acquisition, and therefore there are almost no scientific works that would be devoted to the consideration of methodological aspects of teaching biology and chemistry in distance education.The competency-based learning approach outlined in the State Standard has special cross-cutting skills, namely: reading comprehension, ability to express one's own opinion orally and in writing, critical and systematic thinking, ability to logically justify a position, creativity, initiative, ability to constructively manage emotions, assess risks, make decisions, solve problems, and the ability to cooperate with others. That is why there are changes in the methodological approaches to teaching natural sciences in the context of distance education.The article substantiates the methodological aspects, techniques and features of teaching natural sciences, in particular in biology, chemistry and an integrated course in secondary school. An effective means of improving the quality of the educational process is the widespread introduction of innovations in the study of these disciplines in the context of distance education. This will help to prepare students with high-quality.
Keywords: methodological aspects of teaching, teaching of natural sciences, preparation of students for NMT, science education, educational technologies.